Kriminalisasi Pengobatan Alternatif Menggunakan Kekuatan Ghaib : Analisis Penerapan Pasal 252 KUHP 2023 dalam Melindungi Masyarakat dari Praktik Pengobatan Berbahaya - Ruth Tiur Jovita Kase; Rehnalemken Ginting (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Alternative medicine using supernatural powers is a traditional practice widely found in Indonesia, but it is often conducted without scientific basis, causing negative impacts on society. These impacts include physical, financial, and psychological harm, such as delayed medical treatment leading to fatal outcomes, financial exploitation, and emotional manipulation. Article 252 of the 2023 Penal Code (KUHP) regulates this practice by imposing criminal sanctions on those who violate the law or harm the public. This regulation aims to protect the public, promote transparency, and integrate safe traditional elements into a modern, evidence-based medical system.